Body size and risk of atrial fibrillation: a cohort study of 1.1 million young men. (25th December 2017) - Andersen, K.; Rasmussen, F.; Neovius, M.; Tynelius, P.; Sundström, J.
Abstract: Background: Whilst tall stature has been related to lower risk of vascular disease, it has been proposed as a risk factor for atrial fibrillation. Little is known about other anthropometric measures and their joint effects on risk of atrial fibrillation. Objectives: We aim to investigate associations and potential joint effects of height, weight, body surface area (BSA) and body mass index (BMI) with risk of atrial fibrillation. Methods: In a cohort covering 1 153 151 18‐year‐old men participating in the Swedish military conscription (1972–1995), Cox regression was used to investigate associations of height, weight, BSA and BMI with risk of atrial fibrillation. Results: During a median of 26.3 years of follow‐up, higher height was associated with higher risk of atrial fibrillation (hazard ratio [HR] 2.80; 95% CI 2.63–2.98; for 5th vs. 1st quintile) and so was larger BSA (HR 3.05; 95% CI 2.82–3.28; for 5th vs. 1st quintile). Higher weight and BMI were to a lesser extent associated with risk of atrial fibrillation (BMI: 1.42; 95% CI 1.33–1.52, for 5th vs. 1st quintile). We found a multiplicative joint effect of height and weight. Adjusting for muscle strength, exercise capacity and diseases related to atrial fibrillation attenuated these measures. Conclusions: Higher height and weight are strongly associated with higher risk of atrial fibrillation. These associations are multiplicative and independent of each other and are summarized in a strong association of body surface area with risk of atrial fibrillation. The mechanisms remain unknown but may involve increased atrial volume load with larger body size.